2004
DOI: 10.1074/jbc.m311887200
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Expression of Many Ets Family Transcription Factors and of Potential Target Genes in Normal Mammary Tissue and Tumors

Abstract: The Ets family of transcription factors in mouse or humans is comprised of at least 26 unique family members that contain an evolutionarily conserved DNA binding domain called the Ets domain. The Ets family includes both transcriptional activators and repressors. These factors have been implicated as critical mediators of a wide range of cellular processes, including development, differentiation, growth, and transformation (reviewed in Ref.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
107
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(113 citation statements)
references
References 63 publications
5
107
0
1
Order By: Relevance
“…Following affinity purification, the antibody was tested for specificity by Western blot assay and by immunohistochemical staining of cells from MCF-7 breast tumor cell line and from tissue sections from primary breast and prostate tumors. The data are shown in (11) and of Pse (prostate specific Ets, the mouse homologue of PDEF) mRNA (17). These results together show the specificity of the anti-PDEF antibody as well as its suitability for use in immunohistochemical analysis of PDEF expression in primary tumors.…”
Section: Anti-pdef Antibody Shows Specific Reactivity With Pdefmentioning
confidence: 70%
See 1 more Smart Citation
“…Following affinity purification, the antibody was tested for specificity by Western blot assay and by immunohistochemical staining of cells from MCF-7 breast tumor cell line and from tissue sections from primary breast and prostate tumors. The data are shown in (11) and of Pse (prostate specific Ets, the mouse homologue of PDEF) mRNA (17). These results together show the specificity of the anti-PDEF antibody as well as its suitability for use in immunohistochemical analysis of PDEF expression in primary tumors.…”
Section: Anti-pdef Antibody Shows Specific Reactivity With Pdefmentioning
confidence: 70%
“…Alternatively, since the anti-PDEF antibodies used in two of the three previous studies (19,20) were generated against the full-length PDEF protein, they carried the potential for crossreaction with other Ets factors in the immunohistochemical assay. The latter potential stems from: i) the high degree of sequence homology approaching 45 to 55% amino acid sequence identity in the DNA binding domain between PDEF and other Ets factors (11); and ii) the large number of Ets factors that are expressed in normal mammary gland, and several at much higher levels than Pse or PDEF (17,22). The third study (21) used antibody raised against the same N-terminal segment of PDEF as used in this study, however, the specificity of the immunohistochemical assay for PDEF was not demonstrated in that study.…”
Section: Discussionmentioning
confidence: 99%
“…In pathological processes, the presence of ERM mRNA has been associated with breast cancer metastasis. High levels of this messenger are detected in human and mouse (Galang et al, 2004) metastatic mammary cancer cells. In vivo, in mouse mammary tumors producing high levels of ERM mRNA, ectopic expression of a dominant-negative Ets mutant increases the mouse survival rate (Shepherd et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ese-2, a member of the ESE subfamily of Ets factors, has been recognized as an asthma candidate gene [24], and its expression is correlated with that of the gene encoding maspin, a tumor suppressor protein [25]. Little is known, however, about the role of Ese-2 in gene regulation.…”
Section: Introductionmentioning
confidence: 99%